Prognostic significance of supraclavicular lymphadenopathy in patients with high-grade serous ovarian cancer. Issue 9 (November 2019) - Cybulska, Paulina; Hayes, Sara A; Spirtos, Alexandra; Rafizadeh, Michael J; Filippova, Olga T; Leitao, Mario; Zivanovic, Oliver; Sonoda, Yukio; Mueller, Jennifer; Lakhman, Yuliya; Long, Kara; Chi, Dennis S
Abstract : Objectives: To assess outcomes and patterns of recurrence in patients with high-grade serous ovarian/tubal/primary peritoneal cancers with radiographic supraclavicular lymphadenopathy at diagnosis. Methods: We evaluated all patients with newly diagnosed high-grade serous ovarian cancers treated at our center between January 1, 2008 and May 1, 2013 who had supraclavicular lymphadenopathy (defined as ≥1 cm in short axis) on radiographic imaging (either computed tomography or positron emission tomography) at the time of diagnosis. Results: Of 586 patients with high-grade serous ovarian cancer receiving primary treatment during the study period, we identified 13 (2.2%) with supraclavicular lymphadenopathy diagnosed on pre-treatment imaging. The median age at diagnosis was 52.0 years (range 38.2–72.3). Five (31%) had clinically palpable nodes on physical examination. Four (31%) had a known BRCA mutation. All 13 patients underwent neoadjuvant chemotherapy, followed by interval debulking surgery. Each patient received a median of four cycles of neoadjuvant intravenous chemotherapy (range 3–7). At interval debulking surgery, complete gross resection was achieved in nine (70%) patients, and optimal resection (0.1–1 cm residual disease) in four (30%). Eleven patients (85%) recurred; however, only one (8%) recurred in the supraclavicular lymph nodes. Median follow-up time was 44.3 months (range 22.4–95.0). Median progression-free survival for the cohort was 11.7 months (95% CI 9.2 to 14.1). Median overall survival was 44.3 months (95% CI 41.5 to 47.1). In patients obtaining complete gross resection at interval debulking surgery, median progression-free survival and overall survival were 13.9 months (95% CI 8.9 to 18.9) and 78.1 months (95% CI 11.1 to 145.1), respectively. Conclusions: In our study, approximately 2% of patients with high-grade serous ovarian cancer presented with radiographic evidence of supraclavicular lymphadenopathy. Supraclavicular lymphadenopathy at diagnosis did not portend an unfavorable outcome when complete gross resection was achieved at interval debulking surgery.